Politik Luar Negeri Indonesia dan Malaysia Terhadap China di Era Perang Dingin - Nabil Ahmad Fauzi (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2014)
Since the proclamation on the 1st October 1949, the People's Republic of China has gained an important role in international relations after World War II. The success of communism conquered China, has changed the dynamics of competition between the United States and the Soviet Union that lead the Western Bloc and the Eastern Bloc. The situation has forced the newly independent states in this era, like Indonesia and Malaysia, to determine their position. In addition to facing the same international politics pressures, the two countries also have relations in the domestic issues related to China, namely the existence of the local Communist Party and ethnic of